2012
DOI: 10.1186/1746-4269-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Women care about local knowledge, experiences from ethnomycology

Abstract: Gender is one of the main variables that influence the distribution of local knowledge. We carried out a literature review concerning local mycological knowledge, paying special attention to data concerning women’s knowledge and comparative gender data. We found that unique features of local mycological knowledge allow people to successfully manage mushrooms. Women are involved in every stage of mushroom utilization from collection to processing and marketing. Local mycological knowledge includes the use mushr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
5
37
1
3
Order By: Relevance
“…Other gender-correlated knowledge distribution was found among the Bai (more females thought Rhododendron was important for tourism), the Lisu (more males knew about religion), and the Naxi (males knew about medicine, females knew sayings). This is in agreement with other studies [5] [38] that found patterns of knowledge distribution based on gender.…”
Section: Patterns Of Knowledge Distributionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other gender-correlated knowledge distribution was found among the Bai (more females thought Rhododendron was important for tourism), the Lisu (more males knew about religion), and the Naxi (males knew about medicine, females knew sayings). This is in agreement with other studies [5] [38] that found patterns of knowledge distribution based on gender.…”
Section: Patterns Of Knowledge Distributionsupporting
confidence: 83%
“…Based on the tallying method, more Han females knew about consuming rhododendron than Han males. Because food preparation is traditionally a woman's role [5], it is not surprising that we found that women hold rhododendron knowledge pertaining to these activities. Dulong and Naxi men knew more about using rhododendron for its woody parts compared to their female counterparts.…”
Section: Patterns Of Knowledge Distributionmentioning
confidence: 84%
See 1 more Smart Citation
“…La recolección tiene un alto sentido familiar y comunitario (McLain & Jones, 2005;Villarreal-Ruiz & Castillo, 1996), cuya perspectiva de género no ha sido debidamente investigada, pues las mujeres poseen un vasto conocimiento sobre la taxonomía, biología y ecología local de los hongos (Garibay-Orijel, Ramírez-Terrazo, & Ordaz-Velázquez, 2012) y se encuentran involucradas en la recolección, procesamiento, particularmente, en la comercialización (Pérez-Moreno, Martínez-Reyes, Yescas-Pérez, Delgado-Alvarado, & Xoconostle-Cázares, 2008). Asimismo, son ellas las que fomentan el intercambio de información (Montoya et al, 2008) que se mantiene activo de manera vertical (de padres a hijos) y horizontal (entre gente de la misma generación) (Mariaca et al, 2001), conformando parte de su identidad cultural (Garibay-Orijel et al, 2012) y contribuyendo al mantenimiento de los conocimientos ancestrales (Pérez-Moreno et al, 2008). La recolección de hongos ha demostrado ser compatible con la conservación de los recursos naturales a largo plazo (Toledo, 1992), al lograr una producción continua de los bienes y servicios que el bosque proporciona (Villarreal-Ruiz & Pérez-Moreno, 1989), conformando así un componente ecológico.…”
Section: Introductionunclassified
“…Mushroom harvesting has a high family and community sense (McLain & Jones, 2005;Villarreal-Ruiz & Castillo, 1996), the gender aspect of which has not been duly researched, since women have a vast knowledge of the taxonomy, biology and local ecology of mushrooms (Garibay-Orijel, Ramírez-Terrazo, & Ordaz-Velázquez, 2012) and are involved in their gathering, processing and, particularly, marketing (Pérez-Moreno, Martínez-Reyes, Yescas-Pérez, Delgado-Alvarado, & Xoconostle-Cázares, 2008). They are also the ones that foster the exchange of information (Montoya et al, 2008) that is kept active vertically (from parents to children) and horizontally (among people of the same generation) (Mariaca et al, 2001), forming part of their cultural identity (Garibay-Orijel et al, 2012) and contributing to the maintenance of ancestral knowledge (Pérez-Moreno et al, 2008). Mushroom harvesting has proved to be compatible with long-term conservation of natural resources (Toledo, 1992) by achieving a continuous production of goods and services that the forest provides (Villarreal-Ruiz & Pérez-Moreno, 1989), thus forming an ecological component.…”
Section: Introductionmentioning
confidence: 99%